2007
DOI: 10.1128/iai.00090-07
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Kinetics ofTreponema pallidumDissemination into Blood and Tissues in Experimental Syphilis by Real-Time Quantitative PCR

Abstract: Little is known about the size and kinetics of treponemal burdens in blood and tissues during acquired or experimental syphilitic infection. We used real-time quantitative PCR to measure Treponema pallidum DNA levels in rabbits infected intratesticularly with the prototype Nichols strain. At the outset, we performed a series of in vitro blood spiking experiments to determine the effect of blood processing procedures on the distribution of treponemes in various blood components. T. pallidum DNA levels in plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
44
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 28 publications
9
44
0
Order By: Relevance
“…Our results suggest that the use of the whole-blood fraction would be more effective for the detection of T. pallidum in cases of secondary syphilis (38%), although the results for this fraction were not significantly different from those for the PBMC fraction (31%). Previous studies on rabbit models of syphilis infection reported that whole blood was the best sample for spirochete detection (36) and that T. pallidum was detected in 46% of the whole-blood samples obtained from 57 patients with secondary syphilis (9). This difference in sensitivity may result from the use of a different target gene (tpp47 versus polA) and the conditions in which whole blood was stored, as it has been shown that the freezing of samples may affect sensitivity (9).…”
Section: Discussionmentioning
confidence: 75%
“…Our results suggest that the use of the whole-blood fraction would be more effective for the detection of T. pallidum in cases of secondary syphilis (38%), although the results for this fraction were not significantly different from those for the PBMC fraction (31%). Previous studies on rabbit models of syphilis infection reported that whole blood was the best sample for spirochete detection (36) and that T. pallidum was detected in 46% of the whole-blood samples obtained from 57 patients with secondary syphilis (9). This difference in sensitivity may result from the use of a different target gene (tpp47 versus polA) and the conditions in which whole blood was stored, as it has been shown that the freezing of samples may affect sensitivity (9).…”
Section: Discussionmentioning
confidence: 75%
“…A third possible reason is the choice of specimen or timing of collection. Although the use of peripheral blood mononuclear cell fractions has been described to offer better detection than whole blood (12), this finding was not supported by observations in the rabbit infection model (29). Therefore, further studies with clinical specimens are required to clarify this issue.…”
Section: Discussionmentioning
confidence: 94%
“…A synthetic positive control of 381 bp from the polA gene produced with a pUC57 plasmid was used, as well as a negative control for each run. Confirmation PCR targeting the flaA gene was performed as previously described (10). Over a period of 13 months, 1,706 samples from 1,409 patients were received, of which 887 (52%) were urine samples.…”
mentioning
confidence: 99%